HOMOLOGY MODELING OF SUBCUTANEOUS FILARIASIS DHFR PROTEINS - Chandramore, Kavita (International Journal of Current Pharmaceutical Research, 2017)
Objective: A systematic technique for protein modeling offers great assistance in the study of protein function, dynamics, interactions with ligands, other proteins and even in drug discovery and drug design. Subcutaneous filariasis is rare parasitic disease caused by Loa Loa (eye worm) and monosonallastreptoscerca species.Â Methods: The present study develop three dimensional structure of dihydrofolatereductase present in Loa loa species. For this purpose knowledge based homology modeling is used by using Schrodinger Glide 5.6 software. Results: The procedure involves alignment that maps residues in the query sequence to residues in the template sequence to generate structural model of target, which was further refined and final result validated by using Ramchandran plot. Conclusion: In ramchandran plot majority of the amino acids are in the phi-psi distribution and thedevelop model is reliable and of good quality.